Do conferences drive quality improvement in accounting research? - Muhammad Nur Abdullah Birton; Maryati Maryati; Muhammad Muttaqin (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: In Indonesia, the Simposium Nasional Akuntansi (SNA) and regional accounting conferences (RAC) exist. Prior studies on their database are constrained and predominantly adopt an external viewpoint. Therefore, using an